Effects of Feeder Cells on Dopaminergic Differentiation of Human Embryonic Stem Cells - Zhao, Zhenqiang; Ma, Yanlin; Chen, Zhibin; Liu, Qian; Li, Qi; Kong, Deyan; Yuan, Kunxiong; Hu, Lan; Wang, Tan; Chen, Xiaowu; Peng, Yanan; Jiang, Weimin; et al. (Frontiers in Cellular Neuroscience, 2016)
Mouse embryonic fibroblasts (MEFs) and human foreskin fibroblasts (HFFs) are used for the culture of human embryonic stem cells (hESCs). MEFs and HFFs differed in their capacity to support the proliferation and pluripotency of hESCs and could affect cardiac differentiation potential of hESCs. The aim of this study was to evaluate the effect of MEFs and HFFs feeders on dopaminergic differentiation of hESCs lines. To minimize the impact of culture condition variation, two hESCs lines were cultured on mixed feeder cells (MFCs, MEFs: HFFs =1:1) and HFFs feeder respectively, and then were differentiated into DA neurons under the identical protocol. Dopaminergic differentiation was evaluated by immunocytochemistry, quantitative fluorescent real-time PCR (qRT-PCR), transmission and scanning electron microscopy, and patch clamp. Our results demonstrated that these hESCs-derived neurons were genuine and functional DA neurons. However, compared to hESCs line on MFCs feeder, hESCs line on HFFs feeder had a higher proportion of TH positive cells and expressed higher levels of FOXA2, PITX3, NURR1 and TH genes. In addition, the values of threshold intensity and threshold membrane potential of DA neurons from hESCs line on HFFs feeder were lower than those of DA neurons from hESCs line on the MFCs feeder. In conclusion, HFFs feeder not only facilitated the differentiation of hESCs cells into dopaminergic neurons, but also induced hESCs-derived DA neurons to express higher electrophysiological excitability. Therefore, feeder cells could affect not only dopaminergic differentiation potential of different hESCs lines, but also electrophysiological properties of hESCs-derived DA neurons.